Qualifications of the teacher of the classroom in the recruitment of extra-curricular activities in the educational process from the point of view of educational mentors in Damascus governorate - slman, Razan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Title of the research: Qualifications of the teacher of the classroom in the recruitment of extra-curricular activities in the educational process from the point of view of educational mentors (field study in the schools of the first episode of the basic education district of Damascus) The objective of the research: The aim of the research is to identify the competencies of the teacher in the classroom in the employment of extra-curricular activities in the educational process by defining his competencies in the planning, implementation and evaluation of these activities from the point of view of educational mentors. Research Questions: The main research question was what is the teacher's competence in employing extra-curricular activities in the educational process from the point of view of educational counselors in general? And in each axis of research.? The research was based on the analytical descriptive approach. The research community consisted of the educational supervisors in the Directorate of Education in Damascus Governorate Research tool: The questionnaire used by the researcher was used to identify the views of the educational supervisors on the teacher's qualifications by employing extra curricular activities in the educational process. Results: The results for the first, second, and third questions were found to be the following: The teacher's competencies in planning the extra-curricular activities in the educational process, according to the opinion of the educational supervisors, were found to be moderate. From previous search results we can answer the main search question: The competencies of the teacher in the classroom in the recruitment of extra-curricular activities in the educational process in the field of planning, implementation and evaluation according to the opinion of educational counselors exist, but to a degree.